Study on economics of abandoned building in peninsular Malaysia - Muhamad Samrie, Sakkaran (2019)
The construction industry is one of the most important industry in our nation right now. It is one of the most challenging industries not only in Malaysia but other countries too Generally, it is involving the development of the infrastructure such as building, apartment and house residential. This also resulting to the increasing number of abandoned residential house project. The main issues that faced by the construction industry is abandoned residential house and building project. The term ‘abandoned’ itself show that the building that has been left out or been declined for certain situation or problems during the construction completion work period. There are a lot of effect when the building projects become abandoned such as deflation of our nation economic. This will also affect the environment in way that the abandoned building structure were not utilise and become pollution, health problem, and wastage of resources. This research was aiming to come up with mitigation plan and the objective of this research is to study the causes and effect of abandonment projects in Peninsular Malaysia and analysis the causes in the perspective of house price index. This will also include to propose for the best solution regarding on the abandonment residential projects. This research will be referring to the literature review the mainly focusing on the causes of abandoned building in term of financial problems, disputes among members of the project team, poor management of construction project and so on. The method for this research is using questionnaire survey that distributed to the people that related to the construction industry such as developer, consultants, contractors, etc. The results were analysed using relative index methods and data gathered from the questionnaire will be analysed in order to find the causes of abandonment house projects and to find the best solution for this problem. The result analysed shows that financial problems are one of the main factors contributes to the abandoned building project. As for the solution, the consultant and contractor of the project will be reappoint in hoping that the new appointed consultant will have a stable financial management system. In short, the abandoned house project will be reduced and able to stabilize our nation economy.